Mostra a conta por favor
Anexos:
![](https://pt-static.z-dn.net/files/d2b/54c23dbe771e0b6ce9ef19714fd81c37.jpg)
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
a) (a^2)* (a^7) = a^(2+7) = a^9
b) m³ *m¹ = m^(3+1) = m⁴
c) (y^6)*(y^6) = y^(6+6) = y^12
d) (8^5)/(8^2) = 8^ (5-2) = 8³
e) m²/m = m^(2-1) = m
f) (m^5)/(m^2) = m^(5-2) =m³
g) (a^5)/(a^5) = a^(5-5)= aº= 1
h) (3²)^5= 3^(2*5)= 3^10
i) (a²)^6= a^(2*6)= a^12
j) 5^(-3) = 1/(5^3)
k) 8³ * 8^(-2) = 8^(3-2) =8
l) x^(7) * x^(-3) = x^(7-3) = x^4
m) (m * a ) ² = m² * a²
Perguntas interessantes
História,
7 meses atrás
Matemática,
7 meses atrás
Física,
7 meses atrás
Física,
1 ano atrás
Biologia,
1 ano atrás